Penggunaan AB Mix dan Media Tanam terhadap Viabilitas Tanaman Selada (Lactuca sativa L. Var. New Grand Rapids) dalam Hydroponic Wick System - Imam Safir Alwan Nurza; Diliviva Venesia (Risenologi, 2020)
Indonesia is a country that has abundant natural resources. One of the natural resource wealth is in the agricultural sector. The agricultural sector has a variety of agricultural commodities found in Indonesia. One of them is horticulture. Lettuce (Lactuca sativa L.) is a horticultural commodity. The purpose of this study was to determine the use of ab mix and planting media on lettuce (Lactuca sativa L. var New Grand Rapids) in increasing growth and yield after 40 Days After Planting (HST). This research method is an experiment with statistical data collection and analysis techniques. The results of this study are the number of leaves, plant height, and wet weight in the ab mix is ??higher than aquades (control) because the ab mix provides nutrients for plant growth so that the plant becomes tall and enlarged with its leaves looking wide. However, the number of seeds germinated and plant viability in aquades (control) was higher than ab mix because there was an inorganic salt in ab mix that inhibited seed germination so that the seed membrane in absorbing water became impermeable.